The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1002/eji.200324181
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ regulatory T cells suppress tumor immunity but are sensitive to cyclophosphamide which allows immunotherapy of established tumors to be curative

Abstract: We investigated the mechanisms of immune tolerance raised by tumors by comparing immunogenic and tolerogenic tumor cell clones isolated from a rat colon carcinoma. When injected into syngeneic hosts, the immunogenic REGb cells yield tumors that are rejected, while the tolerogenic PROb cells yield progressive tumors and inhibit the regression of REGb tumors. We show here that PROb tumor volume is correlated with an expansion of CD4 + CD25 + regulatory T lymphocytes in lymphoid tissues. These cells delay in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
644
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 822 publications
(676 citation statements)
references
References 25 publications
19
644
0
7
Order By: Relevance
“…In rodent models, we observed that administration of a low dose cyclophosphamide selectively decreases the number of circulating Treg in cancer-bearing animals and strongly enhances the tumor response to immunotherapy (Ghiringhelli et al, 2004;Taieb et al, 2006;Roux et al, 2008). These preclinical results were later confirmed by other investigators (Liu et al, 2007).…”
Section: Foxp3 þ Treg and Cancer Treatmentsupporting
confidence: 59%
See 1 more Smart Citation
“…In rodent models, we observed that administration of a low dose cyclophosphamide selectively decreases the number of circulating Treg in cancer-bearing animals and strongly enhances the tumor response to immunotherapy (Ghiringhelli et al, 2004;Taieb et al, 2006;Roux et al, 2008). These preclinical results were later confirmed by other investigators (Liu et al, 2007).…”
Section: Foxp3 þ Treg and Cancer Treatmentsupporting
confidence: 59%
“…Experimental data obtained with rodent tumor models demonstrate that Treg reduction can dampen tumor growth and increase the efficacy of tumor immunotherapy (Ghiringhelli et al, 2004). The effects and limitation of targeting Treg in the treatment of cancer was recently reviewed (Zou, 2006;Curiel, 2008).…”
Section: Foxp3 þ Treg and Cancer Treatmentmentioning
confidence: 99%
“…58,59 Tumor-bearing mice show an increased prevalence of Tregs not only at the tumor site but also in the peripheral blood and lymph nodes when compared with normal controls. [60][61][62] Otherwise, selective depletion of these cells may be accomplished following low-dose CTX administration. The administration of this drug at 45-day intervals block the renewal of Tregs in mice with multiple myeloma and enable the restoration of an efficient immune response against the tumor cells, thereby leading to prolonged survival and prevention of disease recurrence.…”
Section: Effects Of Ctx On the Immune Response And Combination With Imentioning
confidence: 99%
“…60,73,74 Paclitaxel PTX is a mitotic inhibitor that causes cell cycle arrest by stabilizing tubulin in microtubules. It is another useful agent for LDM therapy given its broad spectrum antitumor activity and ability to in vitro inhibit endothelial cell functions that are fundamental for angiogenesis.…”
Section: Effects Of Ctx On the Immune Response And Combination With Imentioning
confidence: 99%
“…Data from both preclinical studies and clinical trails highlight that some chemotherapeutic drugs reduce regulatory T-cell (Treg) numbers, although the detailed mechanism of this action remains unknown. These drugs include cyclophosphamide (Cy), [38][39][40] fludarabine 41,42 and gemcitabine, 43 among which, Cy is the best described. In mouse models, it was reported that Cy depletes CD4 1 CD25 1 Tregs, 38 and in vitro studies revealed that Cy reduces the suppressive function of Tregs by decreasing the expression of the transcription factors GITR and FoxP3.…”
Section: Chemotherapymentioning
confidence: 99%